IMPROVING THE FORMATION AND MECHANISMS OF COMPETENCE OF PHYSICAL EDUCATION SPECIALISTS - Mengliyev Bobur Normatovich (American Journals, 2023)
The modernization of physical education content provokes it refocusing not only on the subject competences, but also metasubject, personal, social, communicative, gnostic, projecting, informational and others competences. This contributes the increase in requirements to the system of professional development of physical education teachers who need to successfully meet the educational objectives, showing the completeness and effectiveness of their personal and professional characteristics, the activity of pedagogical thinking and possession of an integrated system of professional skills with a high level of professional competence.Creating the motivational space, initiating individual work of students and assisting them in developing their individual trajectory of self- improvement were the basis of the developed model.
Keywords: Professional competence of physical education teachers, organizational and pedagogical predictive model, the components of activity, the diagnostic tool.